Optical tomography system using infra red sensors - 486325 Mohd. Amri Md. Yunus; Sallehuddin Ibrahim; International conference on Electronic Materials and Packaging Conference (6th. : 2004 : Pulau Pinang) (Skudai : Universiti Teknologi Malaysia, 2004)
40